1994
DOI: 10.1111/j.1539-6924.1994.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

The Risks of “Putting the Numbers in Context”: A Cautionary Tale

Abstract: Despite the warnings of risk communication specialists, members of the technical community often urge that technological risks should be "put in context" by comparisons against risks that are more familiar. Little quantitative evidence is available on the actual behavioral consequences of such risk comparison efforts. In the present study, subjects were presented with two types of information about a hazardous waste incinerator-a simplified statistical summary and a comparison of incinerator risks against the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 12 publications
2
40
0
Order By: Relevance
“…For example, Freudenburg and Rursch (1994) found that explaining a risk of one in 1,000,000 as "less than the risk of smoking a couple dozen cigarettes" made experimental subjects less willing to accept a hypothetical hazardous waste incinerator than they were when the probabilistic information was presented without interpretation. The authors suggest that this may be because the company proposing the incinerator was viewed with suspicion, so a seemingly favorable risk comparison was seen as suspect if provided by a company representative-"Yeah, we've heard that before.…”
Section: Empirical Results Regarding Risk Comparisonsmentioning
confidence: 99%
“…For example, Freudenburg and Rursch (1994) found that explaining a risk of one in 1,000,000 as "less than the risk of smoking a couple dozen cigarettes" made experimental subjects less willing to accept a hypothetical hazardous waste incinerator than they were when the probabilistic information was presented without interpretation. The authors suggest that this may be because the company proposing the incinerator was viewed with suspicion, so a seemingly favorable risk comparison was seen as suspect if provided by a company representative-"Yeah, we've heard that before.…”
Section: Empirical Results Regarding Risk Comparisonsmentioning
confidence: 99%
“…Also, different stakeholders have different preferences about what a forecast should do. Thus efforts to 'educate' the public are unlikely to make them see forecasts as experts do (Freudenburg & Rursch 1994).A more general but related concern is that research should be usable science that has demonstrable social value (Glantz 1996). To qualify, a research program must identify potential users and persuade them of its practical value (Pielke & Glantz 1995).…”
mentioning
confidence: 99%
“…Another way to communicate health risks is to provide messages that describe the connected chain of events that may cause the risk, like a personal testimonial of somebody describing how he/she was confronted with the risk, to make the hazard more vivid (Koehler, 1991). When informing people about unknown risks, the risk could be compared to hazards with similar dimensional profiles (Freudenburg & Rursch, 1994;Visschers et al, 2007). Apart from these presentation formats, there are factors that may influence the effects of risk information such as the qualitative characteristics of the risk (e.g., dread, likelihood, novelty; Skinner et al, 1999;Slovic, 1987), individual differences (e.g., experience, relevance; Rothman & Schwarz, 1998), the described context in which the risk takes place (e.g., culture, society, surroundings; Weber & Hilton, www.intechopen.com 1990), or additional information on, for example, how to deal with possible barriers regarding the recommended health actions (Ruiter et al, 2001).…”
Section: Risk Communication Methodsmentioning
confidence: 99%